Análise biomecânica e densitometria óssea de fêmures de ratos submetidos ao alcoolismo crônico e consumo de fluoreto - Fernandez, Ariane Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The interference of chronic consumption of alcohol on bone metabolism has been reported in several studies. The effect of acute intoxication by alcohol has been widely documented, both in humans and in experimental animals. The aim of this study was to investigate the effects of chronic treatment with alcohol and sodium fluoride in bone tissue of the femur of rats, evaluating the biomechanic and bone densitometry. In the experiment, 105 rats were used, divided into five groups according to a liquid diet administered to them: Group C control (water), Group F (fluoride), Group CA (water and alcohol), Group FA (fluoride and alcohol), CF (Group fluoride for 30 days). All animals were fed commercial ration. In Groups C and F animals were treated with fluoride and water ad libitum, respectively, for a period of 90 days. Groups CA and FA were given, respectively, water and fluoride for 30 days before receiving a solution of sugar cane firewater (40° GL) ad libitum with increasing concentrations of 30% and 60% for 20 days, after which they received plain sugar cane firewater for 40 days until euthanasia of the animal. In the CF group the animals received water for 60 days and then fluoride for 30 days. The animals were killed after 3, 10 and 28 days of completion of the diet; their femurs were dissected, and the right ones were submitted to densitometry analysis on DXA system, while their left ones were submitted to biomechanical testing. Data were submitted to ANOVA and Tukey's test for comparison between groups. Densitometric analysis showed difference between groups in bone mass content (BMC) and bone mineral density(BMD). The order of decreasing BMD was: F, CF, C, FA, CA, showing a statistical difference between groups F and CA. Group F showed the highest BMD and BMC, and CA and FA groups had lower averages in BMC and BMD compared...

A interferência do consumo crônico de álcool no metabolismo ósseo tem sido relatado por diversos estudos. O efeito da intoxicação aguda causada pelo álcool tem sido muito documentado, tanto em humanos quanto em animais experimentais.O objetivo dessa pesquisa foi investigar os efeitos do consumo crônico de aguardente de cana-de-açúcar e fluoreto de sódio em tecido ósseo de fêmur de ratos, avaliando biomecânica e densitometria óssea. No experimento foram utilizados 105 ratos, divididos em cinco grupos, conforme dieta líquida administrada: Grupo C controle (água), Grupo F (fluoreto), Grupo CA (água e álcool), Grupo FA (fluoreto e álcool), Grupo CF (fluoreto por 30 dias). Todos os animais receberam ração comercial. Nos Grupos C e F os animais foram tratados com água e fluoreto ad libitum, respectivamente, por um período de 90 dias. Os Grupos CA e FA receberam respectivamente, água e fluoreto por 30 dias antes da disponibilização de solução de aguardente de cana (40ºGL) ad libitum em concentrações crescentes de 30% e 60% durante 20 dias, após os quais receberam aguardente de cana pura por 40 dias, até a eutanásia do animal. No grupo CF os animais receberam água por 60 dias, e a seguir fluoreto por 30 dias. Os animais foram eutanasiados após 3, 10 e 28 dias de completada a dieta, os fêmures foram dissecados, sendo os direitos submetidos à análise densitométrica no sistema DXA e os esquerdos submetidos ao ensaio biomecânico. Os valores obtidos foram submetidos à análise de variância e teste de Tukey para comparação entre os grupos. Na análise densitométrica foi verificada diferença estatística entre os grupos no Conteúdo Mineral Ósseo (CMO) e Densidade Mineral Óssea (DMO). A ordem decrescente de DMO foi: F, CF, C, FA, CA, sendo observada diferença estatística entre os grupos F e CA. O grupo F apresentou...
Keywords: Densidade óssea; Alcoolismo; Fluoretos; Densitometria; Biomecânica; Bone density